International survey of knowledge, attitudes, and practices of cardiologists regarding prevention and management of cardiac implantable electronic device infections. Issue 11 (20th September 2017) - DeSimone, Daniel C.; Chahal, Anwar A.; DeSimone, Christopher V.; Asirvatham, Samuel J.; Friedman, Paul A.; Baddour, Larry M.; Sohail, M. Rizwan
Abstract: Background: Cardiovascular implantable electronic devices (CIEDs) can be life‐saving. However, complications from CIED infection can be life‐threatening, often requiring device removal. Despite publication of CIED infection management guidelines, there remains marked variation in clinical practice. Objective: To better understand and quantify these differences, we conducted a multinational survey of practitioners of CIED management. Methods: An electronic survey was sent to Heart Rhythm Society members, spanning 70 countries across six continents. All responses were collected anonymously. Results: 227 out of 3, 600 (6.3%) responded to the survey. The majority of surveys were completed by practitioners from the United States (168; 68.3%) and 53.8% of these practiced in academic medical centers. The large majority (92.7%) of sites had protocols to ensure appropriate timing of prophylactic antibiotics. Superficial (incisional) site infections were treated with antibiotics alone 52.5% of the time (consistent with guidelines); in contrast, deep pocket infections were treated with antibiotics (with device removal) in accordance to guidelines only 37.4% of the time. Almost all providers (98.7%) were inclined to perform complete hardware removal in cases of CIED‐related endocarditis. In contrast, 82.2% of survey participants suggested complete CIED system removal in patients with an occult Gram‐positive bacteremia, 65.5% with occult Gram‐negative bacteremia, and 59.3% with prolonged bacteremia due to a source other than CIED. Conclusions: These data suggest wide variability in clinical practice in managing CIED infection with significant deviations from published guidelines. There is critical need to increase awareness and develop institutional protocols to ensure adherence with evidence‐based guidelines to optimize outcomes.